Environmental influences on fish assemblage distribution of an estuarine coastal lagoon, Ria de Aveiro (Portugal) - Pombo, L. (2015)
Fish assemblage was examined for patterns in spatial and seasonal structure within an estuarine coastal lagoon, Ria de Aveiro. Two years of variation in abiotic conditions were recorded to identify factors responsible for maintaining the structure of fish assemblages. Nine sites were sampled monthly with a traditional “chincha” beach-seine net between November 1998 and October 2000. Fish abundance and biomass changed significantly between sites. Temperature was found to be the most important abiotic factor affecting the abundance (number of fish) distribution of fish assemblage, which is more related to seasonal migrations than to spatial migrations. Salinity was the most important abiotic factor affecting the fish biomass, with temperature also having a major influence. The other abiotic parameters analysed also showed some influence on the distribution of fish, although, isolated from the other controlled and/or uncontrolled factors, they could not fully explain all the differences between assemblages. Feeding analysis indicates that fish assemblage is mostly dependent on small benthic and pelagic crustaceans and/or detritus, although they can feed opportunistically on other prey. The low spatial segregation of fish in relation to feeding preference indicates that, in a food-rich lagoon such as Ria de Aveiro, the environmental-biological interactions appear to have a greater effect on fish distribution than do biological interactions.